Induced Bacterial Cross-Resistance toward Host Antimicrobial Peptides: A Worrying Phenomenon - Fleitas, Osmel; Franco, Octávio L. (Frontiers in Microbiology, 2016)
Bacterial resistance to conventional antibiotics has reached alarming levels, threatening to return to the pre-antibiotic era. Therefore, the search for new antimicrobial compounds that overcome the resistance phenomenon has become a priority. Antimicrobial peptides (AMPs) appear as one of the most promising antibiotic medicines. However, in recent years several AMP-resistance mechanisms have been described. Moreover, the AMP-resistance phenomenon has become more complex due to its association with cross-resistance toward AMP effectors of the host innate immune system. In this context, the use of AMPs as a therapeutic option could be potentially hazardous, since bacteria could develop resistance toward our innate immune system. Here we review the findings of major studies that deal with the AMP cross-resistance phenomenon.